Bulk recrystallization for efficient mixed-cation mixed-halide perovskite solar cells. Issue 44 (30th October 2019) - Lin, Liangyou; Wang, Jacob Tse-Wei; Jones, Timothy W.; Grigore, Mihaela; Cook, Andre; deQuilettes, Dane W.; Brenes, Roberto; Duck, Benjamin C.; Anderson, Kenrick F.; Duffy, Noel W.; Wenger, Bernard; Bulović, Vladimir; et al.
Abstract : A facile bulk recrystallization process remove excess PbI2 and improved the performance in perovskite solar cells. Abstract : Today, the use of mixed-cation lead mixed-halide perovskite with a slight excess of lead iodide (PbI2 ) demonstrates the highest device performances in the literature. However, the presence of excess PbI2 in the film poses long-term stability concerns. Here, we propose a facile bulk recrystallization process by applying formadinium chloride (FACl) on perovskite to remove excess PbI2 in the formed crystal. We are able to demonstrate bulk recrystallization, proved and observed by the Grazing incidence XRD to analyze the crystal structure as a function of depth profiling. The reconstructed crystal displays improved optoelectronic qualities with reduced interfacial recombination as well as enhanced device stability. When measured under AM 1.5G spectral conditions the optimized champion device reached a maximum power conversion efficiency (PCE) of 20.2%.